Memorandum of Understanding between the James P. Grant School of Public Health, BRAC University and Achutha Menon Centre for Health Science Studies, Sree Chitra Tirunal Institute for Medicle Sciences and Technology (2008) - James P. Grant School of Public Health, BRAC University (James P. Grant School of Public Health and Achutha Menon Centre for Health Science Studies, 2013)
The James P. Grant School of Public Health, BRAC University, is registered in Dhaka, Bangladesh under the Private University Act of 1992. Henceforth, it is referred to as the JPG-SPH-BU. Sree Chitra Tirunal Institute for Medical Sciences and Technology in Kerala, India is henceforth referred to as SCTIMST. JPG-SPH-BU and SCTIMST are committed to this joint endeavor, but recognize that the envisioned activities are subject to the availability of resources as indicated in the EU Asia Link Contract BD/Asia/ ASIE.. 2006/144465.